Tradisi Peta Kapanca dalam Pernikahan Masyarakat Bima sebagai Media Dakwah (Studi di Desa Naru Barat Kabupaten Bima Provinsi Nusa Tenggara Barat) - Nadirah, Nadirah; Fatoni, Uwes; Rojudin, Rojudin (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
he purpose of this research was to describe the implementation of the Peta Kapanca tradition and to analyze the Peta Kapanca tradition as a medium for Islamic da'wah. This research is included in the type of field research that uses descriptive qualitative methods. The results of the study found that the Peta Kapanca Tradition is a tradition carried out by the Bima community, especially the people of West Naru Village for generations. The Peta Kapanca tradition is included in a series of customary wedding processions for the Bima community. There are 3 processes in carrying out the Peta Kapanca tradition, namely the preparation of event equipment, the implementation of the Peta Kapanca tradition and closing. As a traditional da'wah media, the Peta Kapanca tradition is used as a Nafsiyah (self) da'wah media, Ahliah (family) da’wah media and Fi'ah (group) da'wah media.